Numerical and experimental simulation for air flow and temperature distribution in islamic worship places - Mohamed Abdulwahed Mohamed Khalefa; Esmael Mohamed Ali Ahmed Elbialy; Essam Eldin Khalil; Gamal Elhariry (Cairo : Mohamed Abdulwahed Mohamed Khalefa, 2015)
This research aims to study, analyses and modeling the air flow and temperature distribution inside the an conditioned worship places; specifically those that contain high rise ceiling. The mosque of faculty of engineering - Cairo university has been selected in this thesis to obtain experimental and mathematical models of analytical studies because it has one of air conditioning applications. During the current research, a computer program is used to perform dynamic calculations of fluids (CFL) - computational fluid dynamic program) which its results were published in previous scientific papers and theses. The computational fluid dynamic program can solve conservation of mass, momentum and moment of momentum equations by using different models types such as standard k - f model, RNG model, LVEL model and Chin - Kim model. In this research the standard k - f model was selected according to the results analysis and comparison between different models in addition to best description of turbulence flow patter
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Mechanical Power Engineering
Issued also as CD
Keywords: Experimental; Numerical; Temperature